Causal relationship between hypothyroidism and peripheral neuropathy: a Mendelian randomization study of European ancestry - Duan, Xiping; Zhang, Tianchi; Wang, Ke (Frontiers in Endocrinology, 2024)
Background: Metabolic disorders are significant risk factors for peripheral neuropathy (PN) diseases. However, current clinical observational studies cannot fully determine the causal relationships between hypothyroidism (HT) and PN diseases. Methods: We performed univariate Mendelian randomization (MR) analyses using single nucleotide polymorphisms (SNPs) associated with hypothyroidism and two diseases clinically presented as HT (autoimmune thyroid disease and benign neoplasm of the pituitary gland and craniopharyngeal duct) as instrumental variables. We selected eight peripheral neuropathy diseases (diabetic neuropathy, nerve root/plexus disorder, carpal tunnel syndrome, polyneuropathies, sciatica with lumbago, trigeminal neuralgia, postherpetic neuralgia, small fiber neuropathy) as outcomes. Genetic data were sourced from authoritative genome-wide association study (GWAS) datasets. We primarily used the inverse variance-weighted (IVW) method and conducted a comprehensive sensitivity analysis to ensure robustness. Results: The IVW results indicated that HT was significantly associated with an increased risk of diabetic peripheral neuropathy (OR = 1.22, p = 6.49E-05). HT was also significantly linked to nerve root/plexus disorder (OR = 1.04, p = 6.43E-06) and carpal tunnel syndrome (OR = 1.04, p = 0.004), but appeared to be a potential protective factor for polyneuropathies (OR = 0.93, p = 0.0009). Additionally, autoimmune thyroid disease (AITD) was identified as a potential risk factor for carpal tunnel syndrome (OR = 13.79, p = 0.006) and a protective factor for polyneuropathies (OR = 0.0011; p = 4.44E-5).This study provides genetic evidence supporting potential causal links between hypothyroidism and various peripheral neuropathy diseases.